Hubungan Asupan Karbohidrat dan Status Gizi dengan Kadar Asam Urat pada Lansia di Posyandu Peduli Insani Mendungan Desa Pabelan Kecamatan Kartasura Kabupaten Sukoharjo - Antari, Ranisha Retzi, Setyaningrum Rahmawaty, A., M.Kes., Ph.D, dr. Listiana Dharmawati S., M.Si (2017)
Background : Carbohydrate including fructose and glucose can affect to level of blood uric acid. Overweight could ncrease leptine levels which lead to the increasing of uric acid levels in the blood. Objective : To determine the relationship between carbohydrate intake, nutritional status and blood uric acid of elderly at the Posyandu Peduli Insani Mendungan Pabelan Kartasura Sukoharjo. Research Method : The research was an observational study with cross sectional approach. Sixty-seven elderly were recruited using Simple Random Sampling technique. The data of carbohydrate intake were obtained using semi-quantitative Food Frequency Questionnaire, weight and high was measured using bathroom scale and microtoice, respectively and uric acid levels were analyzed by spectrophotometer using venous blood. Pearson Product Moment test of SPSS for windows version 21.0 was used to analyze the relationship between carbohydrate intake, nutritional status and the uric acid levels of the elderly. Result : Twenty-two (78.6%) elderly have high carbohydrate intake with high uric acid levels and 18 (64.3%) elderly have high nutritional status with high uric acid levels. The result of the correlation test indicated that there is no relationship between carbohydrate intake and nutritional status as well as for carbohydrate intake and uric acid levels of the elderly, with p value 0.073 and 0.078, respectively. Conclusion : Carbohydrate intake and nutritional status are not related to the uric acid levels of elderly at the Posyandu Peduli Insani Mendungan Pabelan Kartasura Sukoharjo Keywords : Carbohydrate Intake, Blood Uric Acid, Elderly Nutritional Status Bibliography : 51 (1992-2015)